Factors Associated with Post Stroke Dysphagia Recommendations in Pakistan: Compliance by Caregivers Perspective - Shakeel, Rimsha; Mumtaz, Nazia; Saqulain, Ghulam; Shakeel, Maryam; Ahmad, Nadeem (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine factors associated with primary care givers’ compliance to post stroke dysphagia and provide recommendations in Pakistan. Study Design: Cross sectional survey Place and Duration of Study: Armed Forces Institute of Rehabilitation Medicine Rawalpindi, Pakistan from Jun 2019 to Apr 2020. Methodology: The study included 92 caregivers which were recruited through purposive sampling. The caregivers were assisting post stroke dysphagia patients of either gender above 18 years of age. Data collection was done using Caregiver Mealtime and Dysphagia Questionnaire (CMDQ). Demographic data was obtained using a basic demographic sheet. Results: Study revealed association of Caregivers compliance to dysphagia recommendations with Patient’s Occupation (p=0.001), Income (p=0.005) and Time Since Onset of Stroke (p=0.050). While no association was noted for Age, Gender, and Education of Patient and Caregiver; Occupation and Income of Caregiver; Type of Palsy and Number of Episodes; Individual Disabilities; Caregiver’s relation with Patient, Time Spent with Patient, Frequency of visits, Marital Status and Area of Origin. Conclusion: There was association of caregivers’ compliance to speech language pathologist’s dysphagia recommendations with Occupation and Income of the patient and Time Since onset with no association with other socio-demographic and clinical characteristics.